Agitation and impulsivity in mid and late life as possible risk markers for incident dementia. Issue 1 (6th September 2020) - Bateman, Daniel R.; Gill, Sascha; Hu, Sophie; Foster, Erin D.; Ruthirakuhan, Myuri T.; Sellek, Allis F.; Mortby, Moyra E.; Matušková, Veronika; Ng, Kok Pin; Tarawneh, Rawan M.; Freund‐Levi, Yvonne; Kumar, Sanjeev; et al.
Abstract: To identify knowledge gaps regarding new‐onset agitation and impulsivity prior to onset of cognitive impairment or dementia the International Society to Advance Alzheimer's Research and Treatment Neuropsychiatric Syndromes (NPS) Professional Interest Area conducted a scoping review. Extending a series of reviews exploring the pre‐dementia risk syndrome Mild Behavioral Impairment (MBI), we focused on late‐onset agitation and impulsivity (the MBI impulse dyscontrol domain) and risk of incident cognitive decline and dementia. This scoping review of agitation and impulsivity pre‐dementia syndromes summarizes the current biomedical literature in terms of epidemiology, diagnosis and measurement, neurobiology, neuroimaging, biomarkers, course and prognosis, treatment, and ongoing clinical trials. Validations for pre‐dementia scales such as the MBI Checklist, and incorporation into longitudinal and intervention trials, are needed to better understand impulse dyscontrol as a risk factor for mild cognitive impairment and dementia.